Design and Development of a Medical Record Management System at Griya Khitan Zaza Banyuwangi - Rohmania, Fadilatul; Prasetyo, Junaedi Adi Prasetyo; Utomo, Agus Priyo; Hakim, Lukman; Ayatullah, Mohamad Dimyati (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
Digitalization in Banyuwangi, particularly in healthcare services, has progressed through the implementation of SI LAJU. Griya Khitan Zaza, which has served over 1000 circumcision patients since 2007 and handles 60 general clinic patients daily, faces significant challenges in managing medical records manually. This manual management of patient medical records is less effective and prone to errors. Therefore, the aim of this research is to develop a comprehensive web-based medical record management system. The creation of this system involves evaluating system requirements, designing a user-friendly interface, implementing the interface design into the program using the Laravel framework, and rigorous testing with the blackbox method using the equivalence partitioning technique. This approach aims to improve operational efficiency and enhance the accuracy of patient data recording, with a test result showing 90.9% effectiveness. The ultimate goal is to significantly improve the quality of healthcare services at Griya Khitan Zaza and contribute to the overall advancement of information technology in the local healthcare sector